Penerapan Arsitektur Tropis pada Kawasan Wisata Permandian Air Panas Di Desa Sonai Kabupaten Konawe - Nola Dzulhijjah; Nahdatunnisa Nahdatunnisa; Machmuddin Muhammad (Arsitektur Universitas Muhammadiyah Kendari, 2022)
Sonai Village has potential that other areas in Konawe do not have in the form of hot springs from the earth. Although it was inaugurated by the government in 2007, the facilities and infrastructure are still very inadequate. Landscape furniture is still very minimal, so information and comfort for tourist visitors have not been fulfilled. This research is a quantitative descriptive research by describing matters related to the subject matter of the primary data approach in the form of observation sheets, existing and interview results, while secondary data is in the form of data from Konawe Regency in numbers, aerial photographs of the Sonai area. 2019. The results show that the Sonai Hot Spring needs to be reviewed in the development of facilities so that visitors can meet the needs and comfort in Sonai Hot Water tourism, with a tropical architecture approach which is a solution for the climate in Indonesia where hot sun, humidity, rainfall, and the wind movement is quite high. The development of a hot spring tourism area must pay attention to the climate of the area, by emphasizing the shape of the building into tropical architecture and using local materials as the main building material is a solution for designing beach tourism in Indonesia, which is predominantly tropical.